Literature Review: Concept and Benefit of ECE Curriculum - Yasminne Nur Annisa Iman; Hibana Hibana (Indonesian Journal of Elementary and Childhood Education, 2025)
This study aims to analyze the concept and benefits of Early Childhood Education (ECE) curricula using a literature review method. Data were gathered from relevant national and international journal articles published within the last ten years, focusing on play-based curricula and holistic learning approaches. The findings indicate that an effective ECE curriculum is designed to support children's comprehensive development, encompassing cognitive, socio-emotional, physical, and moral aspects. Play-based approaches such as multimodal play and serious games have been shown to stimulate creativity, collaboration, and intrinsic motivation. Additionally, nature-based activities promote motor skill development and environmental awareness, while moral and cultural values shape children's character from an early age. The Kurikulum Merdeka, with its freedom-to-learn concept, facilitates exploration and supports 21st-century skills. This study underscores the importance of a holistic approach to ECE curricula in building a strong foundation for optimal child development.